Conformational Space Sampled by Domain Reorientation of Linear Diubiquitin Reflected in Its Binding Mode for Target Proteins. Issue 14 (11th June 2021) - Hou, Xue‐Ni; Sekiyama, Naotaka; Ohtani, Yasuko; Yang, Feng; Miyanoiri, Yohei; Akagi, Ken‐ichi; Su, Xun‐Cheng; Tochio, Hidehito
Abstract: Linear polyubiquitin chains regulate diverse signaling proteins, in which the chains adopt various conformations to recognize different target proteins. Thus, the structural plasticity of the chains plays an important role in controlling the binding events. Herein, paramagnetic NMR spectroscopy is employed to explore the conformational space sampled by linear diubiquitin, a minimal unit of linear polyubiquitin, in its free state. Rigorous analysis of the data suggests that, regarding the relative positions of the ubiquitin units, particular regions of conformational space are preferentially sampled by the molecule. By combining these results with further data collected for charge‐reversal derivatives of linear diubiquitin, structural insights into the factors underlying the binding events of linear diubiquitin are obtained. Abstract : Conformational space of linear diubiquitin under physiological conditions is characterized with paramagnetic NMR restraints, PCS (pseudocontact shift) and RDC (residual dipolar coupling). Alteration of preferentially sampled conformational space caused by charge‐reversal mutations provides insights into structural factors underlying the binding mode of linear diubiquitin.